CO2 Emissions, Economic Growth, Energy Consumption, and Household Expenditure for Indonesia: Evidence from Cointegration and Vector Error Correction Model - Nugraha, Andhyka Tyaz; Osman, Nor Hasni (International Journal of Energy Economics and Policy, 2018)
The present study analyses the causal relationship between CO2 emissions, energy consumption, value added of three development sectors and household final consumption expenditure in Indonesia using annual data from 1975 to 2014. We applied ADF and PP unit root tests, Johansen cointegration test, and Granger causality test based on vector error correction modelling (VECM). Our results indicated that although CO2 emission and energy consumption have a mutual effect, increase CO2 emissions tend given greater effect on energy consumption. CO2 emissions, energy consumption, the value added of industry sector and household final consumption expenditure have a significant effect on the added value of agriculture sector and service sector, while the added value of agriculture sector is a key factor that driven increases the added value of service sector. In the long term, we discover that a cointegration relationship occurring when energy consumption, household final expenditure, and the value added of three development sectors, respectively, are determined as the dependent variables in the model. Based on these results, we concluded that energy conservation and mitigation policies which accompanied the application of energy-saving technologies should be an important priority on the sustainable development planning in Indonesia, especially in order to reduce CO2 emissions and accelerate economic growth rate in Indonesia. Keywords: CO2 emission, Energy Consumption, the value added of development sectors, household final consumption expenditure JEL Classifications: D12, O44, Q43, Q56 DOI: https://doi.org/10.32479/ijeep.7295